Media consumption impact on policies about indigenous people support. Evaluation of Mexican population positioning - Alma Rosa Saldierna; Carlos Muñiz (Estudos em Comunicação, 2012)
In Mexico discriminatory attitudes of the population towards social minorities can still be detected. For Indians, this discrimination causes them to be segregated and forgotten, often lacking political support. In this sense, the media contribute to the formation of stereotypes that affect how we perceive that minority group. It is therefore necessary to know the inﬂuence of the media in Mexico in the construction of stereotypes about Mexican Indians, and how it affects support policies aimed at this segment of the population. The study is based on the paradigm of the Cultivation Theory. We used a telephone survey administered to adult citizens by the states of the republic. Findings showed that media consumption reinforced support for segregationist policies, but in lesser degree than negative stereotypes and racism held by the people.